HIIT is not superior to MICT in altering blood lipids: a systematic review and meta-analysis. Issue 1 (17th December 2019) - Wood, Gina; Murrell, Anna; van der Touw, Tom; Smart, Neil
Abstract : Objective: To compare the effects of moderate intensity continuous training (MICT) and high intensity interval training (HIIT) on adult lipid profiles; to identify training or participant characteristics that may determine exercise-induced change in total cholesterol (TC), triglycerides (TRG), high-density lipoprotein cholesterol (HDL-C) and low-density lipoprotein cholesterol (LDL-C). Design: Systematic review and meta-analysis. Data sources: English language searches of several databases were conducted from inception until September 2019. Eligibility criteria for excluding studies: Inclusion: (1) published randomised controlled human trials with group population n≥5; (2) intervention duration ≥4 weeks; (3) comparing HIIT with MICT; and (4) reporting pre–post intervention lipid measurements. Exclusion: subjects with chronic disease, <18 years, pregnant/lactating, in elite athletic training; and studies with a dietary or pharmaceutical intervention component. Results: Twenty-nine data sets (mmol/L) of 823 participants were pooled and analysed. Neither HIIT nor MICT was better in decreasing TC (0.10 (−0.06 to 0.19), p=0.12, I 2 =0%), TRG (−0.05 (−0.11 to 0.01), p=0.10, I 2 =0%), LDL-C (0.05 (−0.06 to 0.17), p=0.37, I 2 =0%), or TC/HDL-C (−0.03 (−0.36 to 0.29), p=0.85, I 2 =0%). HIIT significantly raised HDL-C (0.07 (0.04 to 0.11), p<0.0001, I 2 =0%) compared with MICT. Conclusion: Neither HIIT nor MICT is superior for altering TC, TRG, or LDL-C, or TC-HDL-C ratio. Compared with MICT, HIIT appeared to significantly improve HDL-C. Clinicians may prescribe either protocol to encourage participation in exercise and reduce cardiovascular risk. To raise HDL-C, HIIT may result in a larger effect size compared with MICT. PROSPERO registration number: CRD42019136722.